The Role of Clinical Laboratory Biomarkers in the Early Detection and Prognosis of Sepsis - Ahmed Asweed Jeryan Al-Anazi; Yasir Ayidh Mohammed Al Mari; Salman Hussain Abdullah Alqahtani; Abdulrahman Hamed Saeed Alghamdi; Ohoud Suliman Matooq Mannaa; Maram Hejjie Eid Alanazi; Abdulaziz Galawi F Alafnan; Ahmed Hejji D Alanazi; Alruwaili, Mohammed Hazzaa T; Alotaibi, Waad Abdulrahman A; et al. (International Journal of Computational and Experimental Science and Engineering, 2024)
Sepsis, a life-threatening condition resulting from the body’s extreme response to infection, requires rapid identification and management to improve patient outcomes. Clinical laboratory biomarkers play a crucial role in the early detection of sepsis by providing valuable diagnostic information. Traditional markers such as white blood cell count and C-reactive protein (CRP) are often supplemented by more specific biomarkers, such as procalcitonin (PCT) and lactate levels, which can indicate an inflammatory response and tissue hypoperfusion, respectively. The timely identification of these biomarkers can aid clinicians in differentiating sepsis from other inflammatory conditions and guide therapy decisions, ultimately improving the chances of survival. In addition to aiding in diagnosis, biomarkers also hold significant promise in prognostication for sepsis patients. Elevated levels of specific biomarkers can indicate the severity of the condition and help stratify patients based on their risk of developing septic shock or multi-organ failure. For instance, biomarkers like interleukin-6 (IL-6) and soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) have been studied for their predictive validity in assessing the severity of sepsis. Monitoring these biomarkers over time can provide insights into a patient’s response to treatment, allowing for timely alterations in therapeutic strategies. As research continues to uncover novel biomarkers and refine existing ones, their integration into clinical practice is poised to enhance our approach to sepsis management, ultimately leading to better outcomes for affected individuals.